Rational Design of Single Molybdenum Atoms Anchored on N‐Doped Carbon for Effective Hydrogen Evolution Reaction. (15th November 2017) - Chen, Wenxing; Pei, Jiajing; He, Chun‐Ting; Wan, Jiawei; Ren, Hanlin; Zhu, Youqi; Wang, Yu; Dong, Juncai; Tian, Shubo; Cheong, Weng‐Chon; Lu, Siqi; Zheng, Lirong; et al.
Abstract: The highly efficient electrochemical hydrogen evolution reaction (HER) provides a promising pathway to resolve energy and environment problems. An electrocatalyst was designed with single Mo atoms (Mo‐SAs) supported on N‐doped carbon having outstanding HER performance. The structure of the catalyst was probed by aberration‐corrected scanning transmission electron microscopy (AC‐STEM) and X‐ray absorption fine structure (XAFS) spectroscopy, indicating the formation of Mo‐SAs anchored with one nitrogen atom and two carbon atoms (Mo1 N1 C2 ). Importantly, the Mo1 N1 C2 catalyst displayed much more excellent activity compared with Mo2 C and MoN, and better stability than commercial Pt/C. Density functional theory (DFT) calculation revealed that the unique structure of Mo1 N1 C2 moiety played a crucial effect to improve the HER performance. This work opens up new opportunities for the preparation and application of highly active and stable Mo‐based HER catalysts.